Environmental Factors Affecting Growth and Occurrence of Testicular Cancer in Childhood: An Overview of the Current Epidemiological Evidence - Fabrizio Giannandrea; Stefania Fargnoli (MDPI AG, 2017)
Testicular cancer (TC) is the most frequently occurring malignancy among adolescents and young men aged 15-34 years. Although incidence of TC has been growing over the past 40 years in several western countries, the explanations for this increase still remain uncertain. It has been postulated that early life exposure to numerous occupational and environmental estrogenic chemicals, such as endocrine-disrupting chemicals (EDCs), may play a contributing role in the etiology of TC, but the subject is still open to additional investigation. Recently, it has also been suggested that prenatal and postnatal environmental exposures associated with child growth and development might also be involved in TC progression. This review of current epidemiological studies (2000-2015) aims to identify environmental factors associated with TC, with a particular focus on infancy and childhood factors that could constitute a risk for disease development. It may also contribute towards recognizing gaps in knowledge and recent research requirements for TC, and to point out possible interactions between child growth and development in relation to prenatal and postnatal environmental exposures.